Seismic Performance of Single Bay Two Storey RC Frame under In-Plane Lateral Cyclic Loading - Nor Hayati, Hamid; M. I., Adiyanto; M, Mohamad (Asian Research Publishing Network (ARPN), 2017)
A half-scale single-bay two-storey RC frame was designed in accordance to Eurocode 8 and constructed using ready mix-concrete by considering seismic load with Ductility Class Medium (DCM). The two-storey moment resistant RC frame was constructed by preparing reinforcement bars caging, preparation of formwork, concreting and curing process. Then, the specimen was tested under in-plane lateral cyclic loading usinga double actuator starting from ±0.01% until ±2.25% with incremental of 0.25% drift. The total number of twenty-four cycles of drift was imposed to RC frame under control displacement method. The visual observations showed that a lot of cracks were concentrated at the corner and exterior beam-column joints where these were the points of transferred the load from top to the bottom of the structure. The ultimate lateral load of 158.48 kN in pushing direction and -126.09 kN in pulling direction was recorded at 2.25% drift. Based on the experimental result, elastic stiffness is 4.04kN/mm, secant stiffness is 1.14kN/mm, effective stiffness is 2.06kN/mm and ductility is 3.51. It can be concluded that the RC moment resistance frame able to withstand minor to moderate earthquake because the value of ductility is ranging between 3 to 6.